Collagen type II–hyaluronan interactions – the effect of proline hydroxylation: a molecular dynamics study. Issue 46 (22nd November 2022) - Bełdowski, Piotr; Przybyłek, Maciej; Bełdowski, Damian; Dedinaite, Andra; Sionkowska, Alina; Cysewski, Piotr; Claesson, Per M.
Abstract : The structural and energetic features of collagen–hyaluronan complexes characterized by different HYP/PRO ratios are described using the molecular dynamics method. Abstract : Hyaluronan–collagen composites have been employed in numerous biomedical applications. Understanding the interactions between hyaluronan and collagen is particularly important in the context of joint cartilage function and the treatment of joint diseases. Many factors affect the affinity of collagen for hyaluronan. One of the important factors is the ratio of 3- or 4-hydroxy proline to proline residues. This article presents the results from molecular dynamics calculations of HA–collagen type II interactions with hyaluronan. The applied protocol employed docking and geometry optimization of complexes built using collagen structures with different numbers of hydroxyl groups attached to proline moieties. It was established that the hydroxyproline/proline ratio affects both structural and energetic features of the collagen–hyaluronan complex. Proline hydroxylation was found to significantly influence the number of all identified types of molecular forces, hydrophobic interactions, water bridges and hydrogen bonds, which can be formed between collagen and hyaluronan. Importantly, an increase in the hydroxyproline/proline ratio in the collagen chain increases the binding affinity for hyaluronan. This is illustrated by the linear correlation between the binding free energy and the hydroxylation degree. A comparison of the results obtained for 3 and 4 hydroxylation of proline indicates that the hydroxyl group attachment position plays a minor role in complex stabilization. However, a slightly stronger affinity was observed for 4 hydroxylation. In order to evaluate the effect of the aqueous environment on the collagen–hyaluronan complex stability, the enthalpic and entropic contributions to the free energy of solvation were analyzed.